2014
DOI: 10.1578/am.40.1.2014.81
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Interactions Between Common Bottlenose Dolphins (Tursiops truncatus) and a Commercial Shrimp Trawler near Savannah, Georgia

Abstract: The common bottlenose dolphin (Tursiops truncatus) has been known to forage in association with shrimp trawlers by feeding on fish caught in or disturbed by nets and on discarded bycatch. In addition, common bottlenose dolphins in the estuarine waterways near Savannah, Georgia display a high rate of begging behavior, and it is hypothesized that interactions between bottlenose dolphins and the shrimp trawl fishery may be a contributing factor. The purpose of this study was to determine which activities of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In front of the Meander River, East Kalymnos was found the area at highest risk of conflict, likely because of high fishing effort and the predominance of trawlers, the gear with the highest overlap with T. truncatus (Table 2). Frequent interactions between trawlers and T. truncatus also occur in Australia (Jaiteh et al, 2013) and the coast of the United States (Greenman, 2012; Kovacs & Cox, 2014). East Kalymnos also has high purse seiner fishing effort, which should reduce the likelihood of conflict with T. truncatus (Marçalo et al, 2015; Wise et al, 2007), although not enough to mitigate risk induced by the large number of trawlers and high total fishing effort.…”
Section: Discussionmentioning
confidence: 99%
“…In front of the Meander River, East Kalymnos was found the area at highest risk of conflict, likely because of high fishing effort and the predominance of trawlers, the gear with the highest overlap with T. truncatus (Table 2). Frequent interactions between trawlers and T. truncatus also occur in Australia (Jaiteh et al, 2013) and the coast of the United States (Greenman, 2012; Kovacs & Cox, 2014). East Kalymnos also has high purse seiner fishing effort, which should reduce the likelihood of conflict with T. truncatus (Marçalo et al, 2015; Wise et al, 2007), although not enough to mitigate risk induced by the large number of trawlers and high total fishing effort.…”
Section: Discussionmentioning
confidence: 99%
“…Using this SCGCS assessment (PBR = 64), the two known commercial dolphin takes that occurred in 1998 and 2002 are not enough to meet the NMFS criteria for classification as a Category II fishery (1% PBR <50% PBR). However, the SCGCS also includes the entire Georgia coast and a recent study found that dolphins frequently associated with shrimp trawlers near Savannah, GA (Kovacs and Cox, 2014). If dolphin takes in Georgia occur at a similar rate as in South Carolina, it may provide enough data to confirm its Category II designation.…”
Section: Indirect Observationsmentioning
confidence: 99%
“…display a remarkably diverse array of individual and cooperative foraging tactics across their global distribution that typically reflect local adaptations to habitat conditions and prey types (Finn et al, 2009; Mann & Sargeant, 2003; Torres & Read, 2009). Specialized foraging methods documented to date include strand feeding (Hoese, 1971; Sargeant et al, 2005), kerplunking (Connor et al, 2000; Nowacek, 2002), cooperative foraging with fishermen (Pryor & Lindbergh, 1990), driver‐barrier feeding (Gazda et al, 2005), foraging in or around trawl nets (Kovacs & Cox, 2014), and using tools, particularly sponges (Krützen et al, 2014; Smolker et al, 1997) and shells (Allen et al, 2011; Wild et al, 2020).…”
Section: Figurementioning
confidence: 99%